Evaluating the Attractiveness of Green Building Quantitative Model of Buyers’ Drivers in Singapore’s Residential Market - Edwin, Tan Wei Ler (Digital Repository of Theses, 2025)
This dissertation explores the factors influencing the adoption of green buildings, with a particular focus on the role of environmental awareness, demographic influences, and barriers to adoption in shaping consumer preferences in the real estate market. The research investigates how various socio-economic variables such as income, education, awareness, prior experience with sustainable properties, and homeownership status impact decisions related to green buildings. The study uses a mixed-method approach, combining both quantitative and qualitative data from surveys and statistical analysis techniques, including regression analysis and chi-square tests. The results indicate that environmental awareness plays a significant role in shaping perceptions of green building features, particularly in influencing attitudes toward sustainability and health benefits. Demographic factors such as income and education are shown to influence the willingness to pay higher initial costs for green buildings, with higher-income individuals more likely to justify these costs based on perceived long-term savings. The findings also suggest that education has a substantial impact on the importance of financial incentives, with more educated individuals demonstrating a greater understanding and appreciation of the financial benefits of green buildings. Barriers such as high initial costs, complexity, and knowledge gaps are significant deterrents for many potential adopters. However, the study finds that prior experience with sustainable properties reduces perceived knowledge and complexity barriers, suggesting that exposure to green buildings can encourage their adoption. Financial incentives and certifications also emerge as critical factors in motivating the decision to purchase green buildings. The analysis emphasizes the need for targeted educational campaigns and the promotion of financial incentives to overcome these barriers and enhance the adoption of sustainable housing practices. Overall, this research highlights the complexity of green building adoption and underscores the importance of a multi-faceted approach, integrating demographic, financial, and educational interventions, to encourage wider adoption and promote sustainability in the housing sector.